"Harmonious" Jones and "Honest John" Shore: Contrasting Responses of Garden Reach Neighbors to the Experience of India. Issue 2 (3rd March 2016) - Franklin, Michael J.
ABSTRACT: The Orientalist Sir William Jones and the Governor-general Sir John Shore were neighbors and close friends in Garden Reach, Calcutta on the banks of the Hugli. Opening with a consideration of their mutual reaction to an imperial neighbor, Bodawpaya, King of Burma, this article explores the differing reactions of long-term East India Company hand, Shore and newly-arrived Crown-appointed Supreme Court judge to the experience that is India. Both keen collectors of Indo-Persian manuscripts, where Shore regretfully found alienating Otherness, Jones excitedly uncovered disconcerting similitude. John Shore, in many ways a straightforward man, was simultaneously something of "a riddle wrapped inside an enigma, " his genuine Orientalist and linguistic interests stunted and deformed by his evangelical convictions. While Jones produced world-modifying ideas and translations which announced the arrival of world literature, Shore's intellectual interest in Vedantism was such that he translated a Persian version of the Yoga Vāsiṣṭha, an important and inherently syncretic text containing elements from Vedantic, Jainite, and Mahāyāna Buddhist traditions. The admiration Shore once felt for Vedantic Hinduism may have evaporated before his fiery conviction that even these sacred writings encouraged "idolatry, obscenity, and vice, " but the sincerity of his desire to save Indian souls remained a guiding light.